Foundations of clinical research applications to evidence-based practice - Portney, Leslie Gross (Philadelphia F.A. Davis, 2020)
The text of this fourth edition has maintained its dual perspectives. It is designed for those who do research to generate new knowledge and examine theories and for those who want to be critical consumers of evidence to inform clinical decision-making. All of us need to be able to critically evaluate research reports to inform practice and further study. The scope of the text allows it to fulfill different needs at different times. This edition will continue to serve this wide audience. It incorporates several important contemporary themes, including the application of evidence-based practice (EBP) for clinical decision-making, the imperative of interprofessional collaboration, the implications of translational research, and the focus of healthcare on quality of life, meaningful outcomes, and patient values. These directions and priorities continue to define research philosophies that guide the conduct of clinical inquiry, the types of questions that are deemed important, and how they influence advances in measurement and analysis techniques"--
Frameworks for generating and applying evidence -- On the road to translational research -- Defining the research question -- The role of theory in research and practice --Understanding evidence-based practice -- Searching the literature -- Ethical issues in clinical research -- Principles of measurement -- Concepts of measurement reliability -- Concepts of measurement validity -- Designing surveys and questionnaires -- Understanding health measurement scales -- Choosing a sample -- Principles of clinical trials -- Choosing a sample -- Principles of clinical trials -- Design validity -- Experimental designs -- Quasi-experimental designs -- Single-subject designs -- Exploratory research : observational designs -- Descriptive research -- Qualitative research -- Descriptive statistics -- Foundations of statistical inference -- Comparing two means : the t-test -- Comparing more than two means : analysis of variance -- Multiple comparison tests -- Nonparametric tests for group comparisons -- Measuring association for categorical variables : chi-square -- Correlation -- Regression -- Multivariate analysis -- Measurement revisited : reliability and validity statistics -- Diagnostic and screening procedures -- Epidemiology : measuring risk -- Writing a research proposal -- Critical appraisal : evaluating research reports -- Synthesizing evidence : systematic reviews and meta-analyses -- Disseminating research.
Includes bibliographical references and index.
Keywords: Biomedical Research -- methods; Evidence-Based Practice -- methods; Research Design; Clinical Decision-Making -- methods; Statistics as Topic -- methods